A proposed evaluation of a membrane separation process using reverse osmosis system analysis (ROSA) software - Costales, Fernandina F.
Seawater desalination offers an alternative solution to water scarcity problems. In fact, a lot of seawater desalination plants are already in existence in countries abroad. This study is conducted to determine the viability of constructing and operating a local seawater desalination plant. THe early stages of the research were described as the selection of suitable site and appropriate desalination technique. THere were three provinces considered under site selection, i.e. Batangas, Bataan and CEbu, and among those three, CEbu emerged to be the most suitable site. Mactan ISland was chosen as the specific location since the area has groundwater resources. Under the process selection, reverse osmosis appeared to be the most appropriate technique for altwater desalination. Its selection was accounted mainly on its economics and its applicability to various types of feedwater.